Orbital Elements and Period Variation of the Eclipsing Binary T LMi - Kyu-Dong Oh (Journal of Astronomy and Space Sciences, 1987)
A photometric solutions of T LMi were derived with derived with the Wilson and Devinney model using the BV photoelectric light curves of Okazaki(1977) and orbital period changes are discussed from the all of the collected times of minima available in the literature. We obtained a variation with a period of 62.y01 and an amplitude of 0.d0425 form the (O-C) diagram. According to the physical properties of T LMi on the basis of derived photometric solution, it have a doubt the credibility of the existence of "R CMs type".